Review of early clinical results and complications associated with oblique lumbar interbody fusion (OLIF). (September 2016) - Phan, Kevin; Maharaj, Monish; Assem, Yusuf; Mobbs, Ralph J.
Highlights: Sixteen articles reporting outcomes for oblique lumbar interbody fusion (OLIF) were included. Fusion rates ranged from 84%–100%. Operative duration ranged from 55–145.1 minutes. Blood loss ranged from 67.8–260 mL. Current studies are limited to small cohort sizes with short-term follow-up. Abstract: Lumbar interbody fusion represents an effective surgical intervention for patients with lumbar degenerative diseases, spondylolisthesis, disc herniation, pseudoarthrosis and spinal deformities. Traditionally, conventional open anterior lumbar interbody fusion and posterior/transforaminal lumbar interbody fusion techniques have been employed with excellent results, but each with their own advantages and caveats. Most recently, the antero-oblique trajectory has been introduced, providing yet another corridor to access the lumbar spine. Termed the oblique lumbar interbody fusion, this approach accesses the spine between the anterior vessels and psoas muscles, avoiding both sets of structures to allow efficient clearance of the disc space and application of a large interbody device to afford distraction for foraminal decompression and endplate preparation for rapid and thorough fusion. This review aims to summarize the early clinical results and complications of this new technique and discusses potential future directions of research.